THE EFFECT OF PLAN TECHNIQUE TOWARD THE STUDENTS’ READING COMPETENCY FOR THE EIGHTH GRADE OF SMP NEGERI 6 SINGARAJA IN THE ACADEMIC YEAR 2013/2014 - ., Ratih Utari Purnama Dewi; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., I Putu Ngurah Wage M, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at knowing the effect of using PLAN technique toward the students’ reading competency for the eighth grade of SMP Negeri 6 Singaraja. For that reason, this study used the experimental approach involving 70 students as the result samples. The instruments used in this study were teaching scenario and reading competency test, and then the data were analyzed descriptively as well as inferentially. The result of the descriptive statistical data analysis showed that the mean score of the experimental group was 81.79, while the mean score of the control group was 73.00. The data showed that the mean score of the experimental group was higher than the mean score of the control group. Besides, the result of the inferential statistics showed that there was a significant difference in reading competency between the experimental group taught through PLAN technique and the control group taught through Conventional Reading technique (t observed 5.428 which was significant at 0.000 (p